Optimizing academic information systems: linking interface design with user satisfaction and loyalty - Khairul Imtihan; Mardi Mardi; Amrullah Amrullah; Baiq Yulia Fitriyani; Muhamad Rodi (Institute of Advanced Engineering and Science, 2026)
Academic information systems (AIS) play a crucial role in supporting academic and administrative processes in higher education institutions. Despite their widespread adoption, sustained user engagement remains a challenge, often linked to usability and system responsiveness issues. This study integrates the technology acceptance model (TAM) with experiential interface dimensions visual quality (VQ) and user interface responsiveness (UIR) to examine their influence on user satisfaction (US) and loyalty within AIS environments. Data were collected from 432 active AIS users across 12 Indonesian universities and analyzed using partial least squares structural equation modeling (PLS-SEM). The results indicate that perceived ease of use (PEOU) and perceived usefulness significantly enhance US, which in turn strongly predicts user loyalty (UL). System responsiveness demonstrates a substantial influence on perceived usability, while usability exerts both direct and indirect effects on long-term user commitment. Although VQ contributes positively to usability perceptions and satisfaction, its direct role in sustaining loyalty is comparatively limited. Importance–performance map analysis (IPMA) further identifies PEOU and UIR as the most strategic priorities for improving long-term engagement. By extending TAM with experiential interface factors, this study offers a more comprehensive framework for understanding AIS adoption and provides practical guidance for designing user-centered, performance-driven AIS.